2006
DOI: 10.1177/1066480706291128
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injury and Postvention: Responding to the Family in Crisis

Abstract: Postvention actions are commonly employed after completed suicides and suicide attempts but can be adapted to assist affected family members in dealing with other types of crisis. The authors adapt a postvention model to be applied to systemically working with families who have a member engaging in self-injurious behavior. Recommendations for counselors who work with youth who self-injure and their families are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…These findings are in line with previous research on DSH [13,16,17] and on more general mental health issues [37], which have identified communication problems within the family as being associated with mental health difficulties and poorer family functioning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in line with previous research on DSH [13,16,17] and on more general mental health issues [37], which have identified communication problems within the family as being associated with mental health difficulties and poorer family functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the findings of previous research on the context of deliberate self-harm of adolescents [16-18], it was found that parental well-being was strongly correlated with the quantity and magnitude of difficulties encountered by the child, as reported by the parent, i.e., parental well-being was lower when child difficulties were greater. These findings may indicate that parents’ mental health is more adversely affected when their child experiences greater difficulties; however, it is also possible that parents whose well-being is lower may be more likely to rate their child’s difficulties as greater, due to their more negative state of mind.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the moderating role of social self-efficacy implies that the treatment of selfinjuring clients may benefit from attention to social skills training and the development of social confidence. Trepal, Wester, and MacDonald (2006) recommended that, when families seek counseling for a self-injuring member, counselors complete a thorough family system assessment, including inquiries into family boundaries and structure. In view of the findings of this study, it may also be beneficial for counselors to assess justice evaluations in the family.…”
Section: Clinical Implications For Family Counselingmentioning
confidence: 99%
“…• Understands and manages countertransference and emotions (Deiter, Nicholls, & Pearlman, 2000;Trepal, Wester, & MacDonald, 2006;White, TrepalWollenzier & Nolan, 2002).…”
mentioning
confidence: 99%